Increased Fetal Plasma Erythropoietin in Monochorionic Twin Pregnancies With Selective Intrauterine Growth Restriction and Abnormal Umbilical Artery Doppler. (10th May 2016) - Chang, Yao-Lung; Chao, An-Shine; Peng, Hsiu-Huei; Chang, Shuenn-Dyh; Su, Sheng-Yuan; Chen, Kuan-Ju; Cheng, Po-Jen; Wang, Tzu-Hao
Abstract : Hypoxia is the primary stimulus for the production of erythropoietin (EPO) in both fetal and adult life. Here, we investigated fetal plasma EPO concentrations in monochorionic (MC) twin pregnancies with selective intrauterine growth restriction (sIUGR) and abnormal umbilical artery (UA) Doppler. We diagnosed sIUGR in presence of (1) birth-weight discordance >20% and (2) either twin with a birth weight <10th percentile. An abnormal UA Doppler was defined as a persistent absent-reverse end diastolic flow (AREDF). The intertwin EPO ratio was calculated as the plasma EPO level of the smaller (or small-for-gestational-age) twin divided by the EPO concentration of the larger (or appropriate-for-gestational-age (AGA)) twin. Thirty-two MC twin pairs were included. Of these, 17 pairs were normal twins (Group 1), seven pairs were twins with sIUGR without UA Doppler abnormalities (Group 2), and eight pairs were twins with sIUGR and UA Doppler abnormalities (Group 3). The highest EPO ratio was identified in Group 3 ( p < .001) but no significant differences were observed between Groups 1 and 2. Fetal hemoglobin levels did not differ significantly in the three groups, and fetal EPO concentration did not correlate with gestational age at birth. We conclude that fetal plasma EPO concentrations are selectively increased in MC twin pregnancies with sIUGR and abnormal UA Doppler, possibly as a result of uncompensated hypoxia.